3D Analyse of the golf swing - Zahalka, F.; Gryc, T.; Maly, T. (14th International Symposium on 3D Analysis of Human Movement, 2016)
Aim of this study was to develop complex 3D model (golfers body and the golf club) which allows observation of all parameters that effects golf swing performance. This complex model could be applied as objectification tool for golf research and practice. For measurement of body segments position during the golf swing were used kinematic analyzer CODA Motion System (Charmwood Dynamics Limited, Leicestershire, England) with recording frequency 400Hz. Four CX1 units were used in laboratory conditions with observing area of 5x3m to record active markers position. To create complex model 32 active markers were placed directly on the body, on the wands and on the golf club. 21 year old female professional golfer (height: 176cm, weight: 68kg) participated in this study. Player has 20 minutes to warm up and play strokes to get used to laboratory conditions. Golf swing performance was evaluated based on golf club speed parameter where we found GCS mean = 27.75 m/s for Driver and GCS mean = 24.26 m/s for 7 iron. Higher GCV for Driver was expected due to length difference between clubs. Kinematic analyzes based on CODA Motion system where complex 3D model of the body was built is suitable to use for analyses of movement in all body segments and the club during the golf swing